Gambaran Kontrol Diri Anggota Bintara Remaja di Polresta Surakarta - Tiara Fadhilah H.F; Sri Ernawati (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Self-control is a major component of the ability to override or change responses within oneself, as well as eliminate undesirable behavioral tendencies and refrain from an action taken. The target of the study was young non-commissioned officers aged 18 to 21 years. The purpose of this study was to determine self-control in young non-commissioned officers of the Surakarta Police. To obtain an overview of the level of self-control in young non-commissioned officers of the Surakarta Police. The number of samples used in this study was 7 people and the data collection techniques used in the study were observation and interviews. The results of this study indicate that the seven young non-commissioned officers of the Surakarta Police have good self-control, the seven members can control themselves with their respective strategies.